Drug-Coated Balloons for Acute Myocardial Infarction: A Metaanalysis of Randomized Clinical Trials - Yuxuan Zhang; Delong Chen; Qichao Dong; Yi Xu; Jiacheng Fang; Huaqing Zhang; Jun Jiang (Journal of Interventional Cardiology)
Background. The role of a drug-coated balloon (DCB) in the treatment of acute myocardial infarction (AMI) is not well established. Methods. Five databases were searched for randomized controlled trials that compared DCB with stents in the treatment of AMI from their inception to 30 July 2021. The primary clinical endpoint was major adverse cardiac events (MACEs). Summary estimations were conducted using fixed-effects analysis complemented by several subgroups. The protocol was registered with PROSPERO (https://clinicaltrials.gov/ct2/show/CRD42021272886). Results. A total of 4 randomized controlled trials with 485 patients were included. On routine clinical follow-up, DCB was associated with no difference in the incidence of MACEs compared with control (risk ratio [RR] 0.59 [0.31 to 1.13]; P=0.11). DCB was associated with similar MACEs compared with drug-eluting stent and lower MACEs compared with bare-metal stent. There was no difference between DCB and control in terms of all-cause mortality, cardiovascular mortality, stent thrombosis, target lesion revascularization, and minimal lumen diameter during follow-up. However, DCB was associated with a lower incidence of myocardial infarction (RR 0.16 [0.03 to 0.90]; P=0.04) and lower late lumen loss (mean difference −0.20 [−0.27 to −0.13]; P<0.00001). Conclusions. In treatment of patients with AMI, DCB might be a feasible interventional strategy versus control as it associated with comparable clinical outcomes. Future large-volume, well-designed randomized controlled trials to evaluating the role of the DCB in this setting are warranted.